"Importancia del dímero en la determinación temprana de Trombosis en pacientes que acuden al Servicio de Emergencia del Hospital Provincial General Docente de Riobamba en el período junio-noviembre de 2014 " - Merino Guaraca, Eder Igor (2016)
The present work is to determine the, importance of technical D-dimer to help diagnose of thrombosis in patients presenting to the emergency Provincial General Teaching Hospital Riobamba, considered one of the diseases most risk in people with problems coagulation, which includes various processes such as clot formation, this is a fibrin network which removes residues of the protein under study, this work consists of general and specific objectives that are closely linked with the issue, it is justified to have extensive knowledge about the disease. The framework is descriptive and explanatory of D-dimmer; All data were analyzed with the technique of Ichroma Dimero-D equipment, also contains tables include illustrative tables and figures that help expose the contents of the investigation, consists of conclusions and recommendations based on this research work, demonstrate the importance of D-dimmer testing in patients with this critical disease when diagnosing deep vein thrombosis, pulmonary embolism or disseminated intravascular coagulation, in this study from June to November 2014 found that the higher incidence of patients with positive results according to gender, 11 males representing 55%. Depending on the frequency of patients attending the emergency service the following data were obtained in both men and women: positive results of 29 people being 59.18% and negative terminals 20 patients with the percentage of 40.82% by total patients treated.